The effect of older population on public health spending: Evidence from Spain - Navarro García, Carlos; Sarria Santamera, Antonio (My University, 2023)
Background: The gradual ageing of the population, and its effect on public spending, constitutes an urgent challenge for advanced economies. Through this study, we analyse the effect of older people, and their health and individual characteristics, on public health spending. Methods: Using logistic regression methods, we have analysed the use of different health services and health technologies by older people in Spain, controlled for several health, socioeconomic, and other individual factors. Results: The main factors that explain the consumption of both health services and health technology, above age, are related to the so¿called need factors: self¿reported health status, presence of chronic diseases, and disability. Conclusion: Knowing the main factors that imply greater public health spending is a topic of special interest for designing efficient health policies, in a context of growth in public health spending. In this way, preventive attention on the so¿called need factors may be an important driver to improve the effectiveness of spending.
Keywords: ageing, health technology, older population, public health spending, Spain, use of health services